Impact of MMP-9 Genetic Polymorphism and Concentration on the Development of Coronary Artery Disease in Ukrainian Population - Oksana S. Pogorielova; Viktoriia V. Korniienko; Yaroslav D. Chumachenko; Olha A. Obukhova; Igor Martsovenko; Viktoriia Yu. Harbuzova (Cardiology Research and Practice)
Coronary artery disease (CAD) is one of the leading causes of death in Europe. It is known that atherosclerosis is the primary risk factor of CAD development. MMP-9 is involved in all stages of atherosclerosis and thus may contribute to CAD emergence. To investigate the influence of MMP-9 on the (CAD) development 25 patients with intact coronary arteries (CA), 40 patients with acute coronary syndrome (ACS), and 63 patients with chronic coronary syndrome (CCS) were enrolled in the study. Real-time PCR was carried out for genotyping on the rs17567-polymorphic locus, and ELISA study was performed to measure the MMP-9 plasma concentration. It was found the lower risk of MI occurrence for AG-carriers (Pa=0.023; ORa = 0.299, 95% CI = 0.106–0.848) in Ukrainian population.